Revisiting the Development of Vaccines Against Pathogenic Leptospira: Innovative Approaches, Present Challenges, and Future Perspectives - Barazzone, Giovana C.; Teixeira, Aline F.; Azevedo, Bruna O. P.; Damiano, Deborah K.; Oliveira, Marcos P.; Nascimento, Ana L. T. O.; Lopes, Alexandre P. Y. (Frontiers in Immunology, 2022)
Human vaccination against leptospirosis has been relatively unsuccessful in clinical applications despite an expressive amount of vaccine candidates has been tested over years of research. Pathogenic Leptospira encompass a great number of serovars, most of which do not cross-react, and there has been a lack of genetic tools for many years. These obstacles have hampered the understanding of the bacteria’s biology and, consequently, the identification of an effective antigen. Thus far, many approaches have been used in an attempt to find a cost-effective and broad-spectrum protective antigen(s) against the disease. In this extensive review, we discuss several strategies that have been used to develop an effective vaccine against leptospirosis, starting with Leptospira-inactivated bacterin, proteins identified in the genome sequences of pathogenic Leptospira, including reverse vaccinology, plasmid DNA, live vaccines, chimeric multi-epitope, and toll- and nod-like receptors agonists. This overview should be able to guide scientists working in the field to select potential antigens and to choose the appropriate formulation to administer the candidates.